VISUALISASI DISTRIBUSI TEKANAN PADA AIRFOIL JOUKOWSKY - Eddy Maryonoto (Universitas Amikom Purwokerto, 2009)
The goal of this research is to develop a computer based system that can beused to visualize pressure distribution on the Joukowsky's airfoil and streamlinespattern around the airfoil. The pressure on the airfoil is calculdted usingformulasderived from potensial theory. Visualization of pressure distribution implementedby using color gradation technique and coded b.v using Borland Delphi 6programming language. The result of the test shotus lhat lhe system has performedperfectly. Pressure dislribution on some kinds of JoukowslE's airfoil shapes andstresmlines pattern around the airfoils can be presenled and seen clearly byusing this visualization system, where the paltern of the pressure distribution onthe airfoil marked by color gradation.